2014
DOI: 10.1080/00958972.2014.963570
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous complexation studies of lead(II) and cadmium(II) with 1,3-bis(tris(hydroxymethyl)methylamino)propane pH buffer

Abstract: Hydrogen buffers are important in biological studies, as a steady hydrogen concentration is of great importance in most scientific studies. One of these buffers is 1,3-bis(tris(hydroxymethyl)methylamino)propane (BTP), which, considering its structure, has complexing capabilities, as previously shown for other metals. In order to know the stability constants for Cd(II) or Pb(II) with BTP, glass electrode potentiometry and direct current polarography studies were carried out. Our results show that both metals fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…TES, TAPSO and tricine have stability constants described for most of the metals. 8,23,25,26,43,[48][49][50][51][52][53][54] Renganathan et al 7 found interferences in Cu inhibition of photosystem II electron transport due to bonding between Cu and TES, Tris and tricine. For TAPSO and TAPS, there is evidence of complexation with Cd, Co, Cu, Pb, Ni and Zn.…”
Section: Tris Familymentioning
confidence: 99%
“…TES, TAPSO and tricine have stability constants described for most of the metals. 8,23,25,26,43,[48][49][50][51][52][53][54] Renganathan et al 7 found interferences in Cu inhibition of photosystem II electron transport due to bonding between Cu and TES, Tris and tricine. For TAPSO and TAPS, there is evidence of complexation with Cd, Co, Cu, Pb, Ni and Zn.…”
Section: Tris Familymentioning
confidence: 99%
“…The model described in the literature for the Cu-BTP system is comprised of three species [CuL, CuL(OH), and CuL(OH) 2 ]. However, the analysis of the structure of BTP (figure 1) together with the models described for other divalent metal-BTP systems [8,9], and the one described in the literature for Cu-BTP system [10] support the idea that this system is not properly described by the current model. N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonic acid (BES) is one of the buffers originally proposed by Good et al [1].…”
Section: Introductionmentioning
confidence: 73%
“…The structure of BTP suggests that it should be a strong complexing agent. In fact, previous studies have shown that BTP forms strong complexes with Cd(II), Co(II), Ni (II), Pb(II), and Zn(II) [8,9], and Cu(II) ions [10]. The model described in the literature for the Cu-BTP system is comprised of three species [CuL, CuL(OH), and CuL(OH) 2 ].…”
Section: Introductionmentioning
confidence: 99%